Relation doctor – patient – from paternalism to partnership - Mielnik-Błaszczak, Maria; Zioło, Anna; Kawiak-Jawor, Ewa (Polish Journal of Public Health, 2011)
Based on literature we have described the transformation of the doctor-patient relationship over the centuries. The work contains analysis of the relation in the sociological perspective. The participants of the relationship are taken back to the transformation of mutual attitudes in direction of the immediate partnership. It shows the relationships between the progress in science and of technology, and the changes taking place. The attitude of the doctor to the patient should take into account patient’s psychophysical whole. The doctor, who can make use the most recent scientific achievements, is bringing relief to the patient in suffering. Together with the reduction of somatic complaints, a patient begins to feel new needs, also in the relation with the doctor. Particular attention was devoted in the study to the peculiar relationship between dentist-patient. It points to the specificity in the general sociological perspective. Increasing the role of the patient in the process of the diagnosis and the treatment is present in the design of more comprehensive approach to health. The move for the promotion of health is putting the primary focus on man’s responsibility for health, thus keeping the appropriate lifestyle.